Application of an accelerometric system for determination of stiffness during a hopping task - Struzik, A.; Zawadzki, J.; Rokita, A.; Pietraszewski, B. (Applied Bionics and Biomechanics, 2020)
Currently, there are several computational methods for stiffness during a hopping task, but they do not necessarily yield the same values. Therefore, it is essential that the simplicity of the equipment used does not affect the measurement validity. The aim of this study is to compare the stiffness values during a hopping task recorded in a laboratory environment and those acquired using the Myotest accelerometer. The measurements were performed on a group of 30 untrained female students (age: 23.0 ± 1.7 years, body height: 1.72 ± 0.07 m, and body mass: 64.8 ± 10.0 kg). According to the manual for the Myotest accelerometric system, each study participant performed three sets of 5 hops. Vertical stiffness was determined based on two measurement methods, one using the Myotest accelerometer and the other using Kistler force plates. The mean value (±SD) of vertical stiffness was 19.0 ± 9.3 kN/m in the countermovement phase and 15.1 ± 5.9 kN/m in the take-off phase. Furthermore, the stiffness determined using the Myotest was 30.7 ± 13.3 kN/m. However, significant relationships between the vertical stiffness in the countermovement phase and the Myotest stiffness (r = 0.79) and between the vertical stiffness in the take-off phase and the Myotest stiffness (r = 0.89) were found. The relationships between the vertical stiffness (in the countermovement and take-off phases) and the stiffness estimated using the Myotest allow us to conclude that despite the significantly overestimated stiffness value, the Myotest accelerometer can still be used for determination of the stiffness trends, e.g., following training. The overestimated stiffness values can result both from inaccuracy in the determination of ground contact time and flight time by the Myotest accelerometer and from the use of an equation that assumes that the movement of the center of mass has a harmonic profile.